Iron level reduction effectivity at Water treatment instalation in Purworejo - Heru Budianto; Tri Joko; Nikie Astorina Yunita Dewanti (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2020)
The iron (Fe) content in drinking water is higher than the standard which can cause technical, physical and health problems. Initial inspection at the outlet of the Drinking Water Treatment Plant in Purworejo showed iron levels of 0.575 mg / lt, so it is necessary to investigate its effectiveness.This study aims to determine the effectiveness of iron reduction level (Fe) in the Drinking Water Treatment Plant (IPAM) in Purworejo. This study uses a descriptive observational method, where data is collected, compiled, interpreted and analyzed so that it provides a complete description of the existing problems and then compares them based on theory, literature review, literature, scientific articles and with applicable regulations..The results of measurements of iron (Fe) levels on an average of 0.976 mg / lt inlet, 0.470 mg / lt outlet and 51.76% effectiveness. Standard iron (Fe) content in Permenkes Number 492 / Menkes / Per / IV / 2010 is a maximum of 0.3 mg / lt. The standard of effectiveness according to the Ministry of Home Affairs Research and Development with a result of 40% - 59.99% is in the ineffective category. The effectiveness of Iron (Fe) reduction in the Drinking Water Treatment Plant in Purworejo is in the ineffective category..